2006
DOI: 10.1002/mrd.20508
|View full text |Cite
|
Sign up to set email alerts
|

Spermatocyte responses in vitro to induced DNA damage

Abstract: Spermatocytes normally sustain many meiotically induced double-strand DNA breaks (DSBs) early in meiotic prophase; in autosomal chromatin, these are repaired by initiation of meiotic homologous-recombination processes. Little is known about how spermatocytes respond to environmentally induced DNA damage after recombination-related DSBs have been repaired. The experiments described here tested the hypothesis that, even though actively completing meiotic recombination, pachytene spermatocytes cultured in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Interestingly, we found that OA treatment of Trip13 Gt/Gt spermatocytes could propel them into MI, despite a report that the same did not occur when wild-type pachytene spermatocytes were treated with the DSB-inducing agents gamma radiation or etoposide [53]. It is possible that the nascent induction of DSBs in pachynema evokes a checkpoint response that cannot be bypassed by OA, whereas the post-strand invasion lesions in TRIP13-deficient spermatocytes do not.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, we found that OA treatment of Trip13 Gt/Gt spermatocytes could propel them into MI, despite a report that the same did not occur when wild-type pachytene spermatocytes were treated with the DSB-inducing agents gamma radiation or etoposide [53]. It is possible that the nascent induction of DSBs in pachynema evokes a checkpoint response that cannot be bypassed by OA, whereas the post-strand invasion lesions in TRIP13-deficient spermatocytes do not.…”
Section: Discussionmentioning
confidence: 62%
“…A third possible endogenous source of DSBs is impaired topoisomerase II activity. Inhibition of topoisomerase II activity in pachytene spermatocytes has been found to result in DSB formation, indicating that topoisomerase II is indeed functional in meiocytes [68]. Fourth, endonuclease activity of ORF2, encoded by Line1 transposons, generates DSBs during the transposition of mobile elements in the genome [69][71].…”
Section: Discussionmentioning
confidence: 99%
“…This is a potent genotoxic Topo IIα inhibitor used in cancer therapy, whose effect lies in blocking the activity of Topo IIα once it has cut the concatenated DNA molecules, but prior to the occurrence of the religation (Nitiss 2009b). It has been reported that ET-mediated inhibition of Topo IIα during mouse meiosis induces alterations on homologous recombination during prophase I, fragmentation of centromeric satellite DNA, and failures in chromosome segregation during meiotic divisions (Kallio and Lähdetie 1996;Marchetti et al 2001;Russell et al 2004, Matulis andHandel 2006). Altogether, these data suggest that Topo IIα has a role in chromosome segregation during mouse meiotic divisions, as in mitosis.…”
Section: Introductionmentioning
confidence: 99%